2014
DOI: 10.3109/14767058.2014.986450
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in women aged 35 years or older with gestational diabetes – a registry-based study in Finland

Abstract: GDM at advanced age is a high risk state and, more specifically, the risk caused by age and GDM appear to be increasing in preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 14 publications
3
19
1
Order By: Relevance
“…This study reported no significant higher incidence of GDM among the mothers belonging to advanced age group. It is not in concurrence with what was found in the study carried out by Pattnaik L et al 12 as well as Lamminpaa R et al 16 It also agrees with the study of Carolon M et el. 17 Analysis of this study revealed an increased incidence of hypothyroidism in advanced age mothers consistent with the observation made by Pattnaik L et al 12 The possible reason might be an increased incidence of autoimmune thyroiditis with advanced age.…”
Section: Discussionsupporting
confidence: 77%
“…This study reported no significant higher incidence of GDM among the mothers belonging to advanced age group. It is not in concurrence with what was found in the study carried out by Pattnaik L et al 12 as well as Lamminpaa R et al 16 It also agrees with the study of Carolon M et el. 17 Analysis of this study revealed an increased incidence of hypothyroidism in advanced age mothers consistent with the observation made by Pattnaik L et al 12 The possible reason might be an increased incidence of autoimmune thyroiditis with advanced age.…”
Section: Discussionsupporting
confidence: 77%
“…Maternal age and BMI in GDM are the two most widely studied factors owing to their importance in establishment of the disease [31][32]. Lately, increasing obesity incidences have been a cause of rising concern since high BMI positively correlates with hypertensive disorders in pregnant females [32].…”
Section: Population Screeningmentioning
confidence: 99%
“…Researchers also found a relationship between a woman's body mass index (BMI) and shoulder dystocia; women with elevated BMIs at the time of childbirth were often at increased risk for the condition (Cheng et al, 2013;Cheng et al, 2006;Gupta et al, 2010;Schummers, Hutcheon, Bodnar, Lieberman, & Himes, 2015), and one group of researchers found that women with BMIs greater than or equal to 30 kg/m 2 had a nearly three times greater risk (Mazouni et al, 2006). Chronic diabetes (Abell et al, 2016;Boghossian et al, 2014;Shand, Bell, McElduff, Morris, & Roberts, 2008;Son, Lim, Lee, Cho, & Park, 2015) and gestational diabetes (Burkhardt, Schmidt, Kurmanavicius, Zimmermann, & Schaffer, 2014;Dodd et al, 2012;Lai et al, 2016;Lamminpä ä et al, 2016;Ovesen et al, 2015;Øverland et al, 2012;Tsur et al, 2012) were also associated with increased risk for shoulder dystocia. Whether the effect of the latter may be mitigated by treatment is not yet clear.…”
mentioning
confidence: 99%